Effect of osmotic stress on the expression of TRPV4 and BKCa channels and possible interaction with ERK1/2 and p38 in cultured equine chondrocytes - Hdud, Ismail M.; Mobasheri, Ali; Loughna, Paul (American Physiological Society, 2014)
The metabolic activity of articular chondrocytes is influenced by osmotic alterations that occur in articular cartilage secondary to mechanical load. The mechanisms that sense and transduce mechanical signals from cell swelling and initiate volume regulation are poorly understood. The purpose of this study was to investigate how the expression of two putative osmolyte channels [transient receptor potential vanilloid 4 (TRPV4) and large-conductance Ca2+-activated K+ (BKCa)] in chondrocytes is modulated in different osmotic conditions and to examine a potential role for MAPKs in this process. Isolated equine articular chondrocytes were subjected to anisosmotic conditions, and TRPV4 and BKCa channel expression and ERK1/2 and p38 MAPK protein phosphorylation were investigated using Western blotting. Results indicate that the TRPV4 channel contributes to the early stages of hypo-osmotic stress, while the BKCa channel is involved in responding to elevated intracellular Ca2+ and mediating regulatory volume decrease. ERK1/2 is phosphorylated by hypo-osmotic stress (P < 0.001), and p38 MAPK is phosphorylated by hyperosmotic stress (P < 0.001). In addition, this study demonstrates the importance of endogenous ERK1/2 phosphorylation in TRPV4 channel expression, where blocking ERK1/2 by a specific inhibitor (PD98059) prevented increased levels of the TRPV4 channel in cells exposed to hypo-osmotic stress and decreased TRPV4 channel expression to below control levels in iso-osmotic conditions (P < 0.001).